Magnetohydrodynamic Computer Simulation of Erupting Low Solar Coronal Magnetic Fields - Setiahadi, Bambang (Universitas Muhammadiyah Surakarta, 2017)
An analytical solution of initial and un-sheared low solar coronal magnetic arcade as initial value isperturbed and equilibrium is assumed to loss. The dynamical state of lossing equilibrium is descibed first andpossible consequnces to the numerical scheme is derived. The dynamical evolution is followed by computersimulation which computed numerical solutions of complete set time-dependent magnetohydrodynamicspartial differential equations. Automatic algorithm to inspect the MHD fast-mode speed is introduced tomaintain simulation scheme stable during computations. Results show there will be shocks, known as MHD- waves shock, along the way to interplanetary space. Temperature shock is not prominent and only arelatively unsignificant temperature rise is resulted, instead density shock is noticeable. The density rise isrelatively far greater to order of kg 9 1.010 .